2004
DOI: 10.1002/hon.737
|View full text |Cite
|
Sign up to set email alerts
|

Isolated central nervous system blast crisis in chronic myeloid leukemia

Abstract: Chronic myeloid leukemia is a myeloproliferative disorder characterized by the presence of the Philadelphia chromosome, t(9:22). Extramedullary blast crisis is a rare event. Imatinib mesylate has become the treatment of choice, especially for patients for whom allogenic stem cell transplantation is not an option. Imatinib produces complete cytogenetic responses in excess of 80%. However, the penetration of the drug and its metabolites into the CNS (Central Nervous System) is poor. Hence for patients who are on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 4 publications
0
53
0
2
Order By: Relevance
“…Though several case reports of CNS blast crisis in CML patients on Imatinib have been published from west [1,10,11], only limited Indian case reports are available [2,12]. On reviewing the literature it was found that in several studies [2,8,12], headache, vomiting were the common presenting features of CNS involvement and was seen in both our patients.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Though several case reports of CNS blast crisis in CML patients on Imatinib have been published from west [1,10,11], only limited Indian case reports are available [2,12]. On reviewing the literature it was found that in several studies [2,8,12], headache, vomiting were the common presenting features of CNS involvement and was seen in both our patients.…”
Section: Discussionmentioning
confidence: 66%
“…It has become the treatment of choice of CML in chronic phase especially for patients for whom allogenic stem cell transplantation is not an option [2,3]. It has also shown activity in CML patients in the accelerated phase or blast crisis [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations